Maryland's Global Hospital Budgets: Impacts on Medicare Cost and Utilization for the First 3 Years. Issue 6 (June 2019) - Beil, Heather; Haber, Susan G.; Giuriceo, Katherine; Amico, Peter; Morrison, Marisa; Beadles, Christopher; Berzin, Olivia; Cole-Beebe, Maggie; Greenwald, Leslie; Jiang, Linda; Perry, Rebecca; Wright, Alton
Abstract : Background: Global budgets have been proposed as a way to control health care expenditures, but experience with them in the United States is limited. Global budgets for Maryland hospitals, the All-Payer Model, began in January 2014. Objectives: To evaluate the effect of hospital global budgets on health care utilization and expenditures. Research Design: Quantitative analyses used a difference-in-differences design modified for nonparallel baseline trends, comparing trend changes from a 3-year baseline period to the first 3 years after All-Payer Model implementation for Maryland and a matched comparison group. Subjects: Hospitals in Maryland and matched out-of-state comparison hospitals. Fee-for-service Medicare beneficiaries residing in Maryland and comparison hospital market areas. Measures: Medicare claims were used to measure total Medicare expenditures; utilization and expenditures for hospital and nonhospital services; admissions for avoidable conditions; hospital readmissions; and emergency department visits. Qualitative data on implementation were collected through interviews with senior hospital staff, state officials, provider organization representatives, and payers, as well as focus groups of physicians and nurses. Results: Total Medicare and hospital service expenditures declined during the first 3 years, primarily because of reduced expenditures for outpatient hospital services. Nonhospital expenditures, including professional expenditures and postacute care expenditures, also declined. Inpatient admissions, including admissions for avoidable conditions, declined, but, there was no difference in the change in 30-day readmissions. Moreover, emergency department visits increased for Maryland relative to the comparison group. Conclusions: This study provides evidence that hospital global budgets as implemented in Maryland can reduce expenditures and unnecessary utilization without shifting costs to other parts of the health care system. Abstract : Supplemental Digital Content is available in the text.